A molecular phylogeny of Equatorial African Lacertidae, with the description of a new genus and species from eastern Democratic Republic of the Congo - Greenbaum, Eli (2011)
Currently, four species of the lacertid lizard genus Adolfus are known from Central and East Africa. We sequenced up to 2,825 bp of two mitochondrial (16S and cyt b) and two nuclear (c-mos and RAG1) genes from 41 samples of Adolfus (representing every species), two species each of Gastropholis and Holaspis, and in separate analyses combined this data with GenBank sequences of all other Eremiadini genera and four Lacertini outgroups. Data from DNA sequences were analyzed with maximum parsimony (PAUP), maximum-likelihood (RAxML) and Bayesian inference (MrBayes) criteria. Results demonstrated that Adolfus is not monophyletic: A. africanus (type species), A. alleni and A. jacksoni are sister taxa, whereas A. vauereselli and a new species from the Itombwe Plateau of Democratic Republic of the Congo are in a separate lineage. Holaspis and Gastropholis were recovered in separate clades. Based on this molecular data, relatively substantial sequence divergence and multiple morphological differences, we describe a new genus of lacertid for the lineage including A. vauereselli and the new Itombwe species. The recognition of this new, endemic genus underscores the conservation importance of the Albertine Rift, especially the Itombwe Plateau, a unique region that is severely threatened by unchecked deforestation, mining and poaching.